Estudo pessoa-ambiente-gênero a partir da vivência das terras caídas numa várzea amazônica: análise do afeto ao lugar em Fátima de Urucurituba no eixo Forte/Santarém-PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2020)
The environmental issue is extremely complex, which impels us to plan studies that focus on an integrating vision of the dialectic processes of the relationship between society, nature and development, especially with regard to the Amazon. Environmental Psychology has consolidated itself as a fertile area for interdisciplinary discussions, expanding knowledge related to human-environmental problems. The present thesis focused its attention on the psychosocial and socioenvironmental implications arising from the phenomenon of "fallen lands" in the lowland santarena experienced by the community members of Fátima do Urucurituba, resettled on the mainland in the municipality of Santarém/PA. As a general objective, he proposes “To analyze the person-environment-gender relations based on the understanding of the affection for the place in a lowland riverside community, which experienced the phenomenon of fallen lands in the Santarena Amazon”; and assumes the following specific objectives: i) to identify the socioenvironmental profile of the Fátima de Urucurituba community members in the stronghold; ii) understand the space appropriation actions carried out by the community members; iii) to investigate the affective relationship of community members resettled to the community currently constituted and iv) to verify the implications of the phenomenon of “fallen lands” on territorial change and on socioeconomic issues. The research used a quanti-qualitative approach, with structured interviews with 17 families, application of the instrument for generating affective maps with 12 community members and participant observation. The analysis of the data revealed a new socio-environmental context of the Fátima de Urucurituba community members resettled on the mainland, namely: impacts on individual and collective sociability through the reconfiguration of the territory; changes in socioeconomic activities; men and women experienced territorial change differently and developed different affections for the place of residence. Resettlers show a strong community relationship and bring elements of their collective identity from the old community; demonstrate several appropriation actions with space; potentializing estimates of affection, as well as a process of building a new place identity in the current socio-environmental context. The "fallen lands" in the Amazon is a socio-environmental and political event that affects the most vulnerable populations and is complex, showing the urgency of public policies for managing the territory and the lack of guarantee of fundamental rights. This thesis intends to produce references in Environmental Sciences in a psychosocial and affective perspective, with respect to the populations of the Amazon.
Keywords: Psicologia ambiental; Amazônia; Ciências Ambientais; Terras caídas; Relações de gênero; IMPACTOS AMBIENTAIS E SOCIAIS DA MUDANÇA DO USO DA TERRA NA AMAZÔNIA